PENINGKATAN KEMAMPUAN MEMAHAMI TEKS BACAAN BAHASA JERMAN DENGAN TEKNIK SCANNING READING - Haslinda Haslinda (Jurnal Panrita, 2021)
The problem of this research is about the low ability to understand German reading texts. It aims to find out the results of increasing the ability to understand German reading texts with scanning reading techniques at SMA Negeri 10 Makassar. This research is classified into classroom action research. Data collection techniques were obtained through observation, documentation analysis, and the reflection stage. The results showed that the scanning reading technique could improve the ability to understand German reading texts for class XI IPA 1 SMA Negeri 10 Makassar. In the first cycle, it was found that 32 (80%) students had reading speed using scanning reading techniques with low qualifications, while 8 (20%) students had moderate reading skills. At the level of understanding in the medium category are as many as 31 (77.5%) students and the level of understanding in the high category are as many as 9 (22.5%) students. In the second cycle, it was found that all students, as many as 40 (100%) students were declared successful in reading with the scanning reading technique with moderate qualifications. Meanwhile, the level of understanding in the very high category was 6 (15%) students and those with the high category were 34 (85%) students and none of the students had a very low level of understanding. This means that the level of understanding German texts with the scanning reading technique of class XI IPA 1 SMA Negeri 10 students in cycle II is declared successful